A novel urea-derived fluorescent sensor for highly selective and sensitive detection of Fe3+. Issue 30 (27th July 2016) - Wu, Xingxing; Zhang, Shanshan; Niu, Qingfen; Li, Tianduo
Graphical abstract: Highlights: A reversible and fast-responsive urea-based fluorescent sensor for Fe 3+ was synthesized. Sensor MDSU displayed a high selectivity and sensitivity for Fe 3+ . This sensor can detect Fe 3+ in real time in aqueous solution. The low detection limit was 1.816 × 10 −7  M. Abstract: A novel urea-derived fluorescent sensor MDSU for Fe 3+ was designed and synthesized. Its sensing behavior to metal ions was investigated by absorption and fluorescence spectra. In DMSO/H2 O (1:1, v/v) solution, sensor MDSU showed a highly selective and sensitive recognition to Fe 3+ over other competitive metal ions. This sensor formed a 1:1 complex with Fe 3+ and displayed fluorescence quenching. Moreover, sensor MDSU can rapidly detect Fe 3+ in real time with a lower detection limit of 1.816 × 10 −7  M.